How intellectuals censor the intellect: (mis-)representation of traditional history and its consequences - Daneshgar, Majid (2019)
Abstract: This essay will explore how the intellects of both scholars and their audiences are censored. In addition to various Western thinkers, particular attention will be paid to Ali Shari'ati, one of the most influential thinkers of modern Iran, and how he represented an important Islamic tradition. Not only did his ideas inspire revolutionary acts by generations of Iranians, but Turkish, Arab, Malay, Indonesian, and Indian philosophers, sociologists, theologians, and politicians have all employed his definitions of concepts such as justice, injustice, revolution, corruption, and bliss. This article sheds light both on how intellectuals influence their audience, and their long-term impact on broader communities. In order to do so, it will analyze the material and political conditions that censor both what scholars are able to say, and what their audiences are allowed to hear